DETERMINATION OF SHIO APPLICATION PROGRAMMING USING VISUAL BASIC 6.0 - Marhara Jaya Putra; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2002)
Your sign is the most important aspect of interpreting someone's personality. Many people determine the sign just by looking at just the birth year. This is becauselack of insight and interest in the community about the determination of the sign.This application is made to facilitate the public in determining the sign based on the date, month, year-born person. And provide information about the personality, talent, love and health. Other than that this application is made with visual basic 6.0 programming with the intention that the resulting appearance of this application is the user interface, so easy to use by various types among the users (the user).